An Investigation in Understanding the Influence of Brand Preferences on Purchase Intention: Examples of Indonesian Women’s Apparel Brand - Sultan, Fatmarani; Setiawati, Lina (Politeknik Negeri Bandung, 2024)
This study aims to investigate the factors influencing brand preferences in the purchase intention of Indonesian women’s apparel brands. The data were collected through a questionnaire distribution of 422 respondents from Indonesian women’s apparel brand consumers and processed with the Structural Equation Model - Partial Least Square (SEM-PLS). Brand preferences in selecting and purchasing women's apparel are influenced by satisfaction, extrinsic cues, and brand trust. On the contrary, intrinsic cues do not affect brand preferences in purchase intention because extrinsic cues can dominate more, consumers desire to save more time, and there are rapidly fast fashion trends. Moreover, brand preferences have a greater impact on purchase intention. Women's apparel brands can shape the brand preferences of their consumers based on the influencing factors to dominate the market competition. This study contributes to the literature on brand preferences in choosing women's fashion behavior. This is one of the pioneering studies to empirically examine the influence of cues and brands in the context of the desire of the Z generation to purchase women's apparel in an emerging market such as Indonesia.